The influence of N-doping types for carbon nanotube reinforced epoxy composites: A combined experimental study and molecular dynamics simulation - Jung, Hana; Choi, Hoi Kil; Kim, Soyoung; Lee, Hun-Su; Kim, Yonjig; Yu, Jaesang (ELSEVIER SCI LTD, 2017)
In this study, nitrogen doped carbon nanotube reinforced epoxy nanocomposites were characterized through experiments and molecular dynamics (MD) simulation. Carbon nanotubes were functionalized by nitrogen inductively coupled plasma. They were made into a nanocomposite by a solvent-free mixing method. The various characteristics of nanocomposites, including nitrogen doped carbon nanotubes were analyzed by the following experiments: a Raman spectra, an X-ray photoelectron spectroscopy (XPS), quasi-static tensile tests, a scanning electron microscopy (SEM), and a transmission electron microscopy (TEM). In addition, an MD simulation was performed to predict the mechanical properties of nanocomposites and the results were compared to the test measurements. It showed that the effective dispersion of nitrogen doped carbon nanotubes was important to improve the mechanical characteristics of the nanocomposites. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: MECHANICAL-PROPERTIES; GRAPHENE; NANOCOMPOSITES; LENGTH; FIBER; SIZE